A HEALTHY LIFESTYLE IS THE GUARANTEE OF HEALTH WITHOUT DRUGS - Ismoilov Komil Tuygunovich; Shukrullayeva Mexribon Ulugbekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article reflects on a healthy lifestyle, proper nutrition, adherence to daily routine, timely rest, as well as the regime and rules implemented in this process.